„Jen je škoda, že víme, jak to s Husem dopadlo.“ Šestisté výročí upálení Jana Husa v české vzpomínkové kultuře || "It's a shame we know what happened to Hus." The six hundred years' anniversary of the death of Jan Hus in the Czech memory culture - Kateřina Sixtová (Historie - Otázky - Problémy, 2018)
The text explores the portrayal of Jan Hus in the context of the 600th anniversary of his death, which was commemorated in the year 2015. The author analyses different media used for commemoration of Jan Hus from the perspective of Memory Studies.